Analisis Daya Dukung Sumber Daya Air DAS Kahayan - Christian Aditiya Nugraha Putra; Nomeritae; Raden Haryo Saputra (Jurnal Serambi Engineering, 2024)
A river basin, which is a unit of rivers and tributaries, has the hydrological functions of a watershed to drain water, support peak rainfall events, release water gradually, and maintain water quality and quantity. Over time, increasing population growth and relatively rapid economic growth have led to increased water demand in various sectors, both domestic and non-domestic. The focus of this research is the carrying capacity of water resources in 8 sub-districts in the Kahayan watershed, Central Kalimantan Province, consisting of the subdistricts of Banama Tingang, Kahayan Tengah, Jabiren Raya, Rakumpit, Bukit Batu, Jekan Raya, Pahandut and Sebangau. The aim of this study is to compare the potential water availability and demand, and the status of the carrying capacity of water resources in each sub-district. Water availability calculations were simulated based on rainfall and climate data using the F.J. Mock method, while water demand was calculated based on different types of water demand. An analysis of the carrying capacity of water resources in the Kahayan catchment was calculated based on a comparison of potential water availability Q mainstay with water demand. The total water availability in 2027 would be 4,972,375,728 m3/year compared to a total water demand of 587,180,300,648 m3/year and the total water availability in 2032 would be 4,972,375,728 m3/year compared to a total water demand of 588,020,671,827 m3/year. A comparison of total water availability and total water demand in 2027 and 2032 shows that the carrying capacity of water resources in the Kahayan Basin would be in surplus status.